LE SOLEILNOIRPOINT DE CHARLES NOKAN : UNE ESTHÉTIQUE DRAMATIQUE SUBVERSIVE - Koffi Logba Konan Dominique (European Scientific Journal, ESJ, 2014)
Beyond subversive plastic presentation of theatrical text, Black Sun spot is revealed as the precursor piece of political theater in Côte d'Ivoire. Charles Nokan it sifts through a neo-colonial power which oppresses, enslaves and degrades people. Its societal ideal is to know the oppressed of all backgrounds come out of their lives incarcerated forever, he convened the original characters in the play to throw off the yoke and snatch freedom to the three foundations: intellectual, political struggle and economic struggle. With Black Sun point play on the edge of colonial theater and Ivorian postcolonial theater Nokan inaugurates a new aesthetic drama that fits into modernity.